LEGAL ANALYSIS OF THE USE OF ELECTRIC BIKES ACCORDING TO LAW NUMBER 22 OF 2009 AND REGULATION OF THE MINISTER OF TRANSPORTATION OF THE REPUBLIC OF INDONESIA NUMBER PM 45 OF 2020 - Soares, Duarte Tilman; Putra, I Komang Adi (Kerta Dyatmika, 2025)
The presence of electric bicycles brings a new mobility approach that also colors the global transportation sector. In its operation, electric bicycles are indeed designed as environmentally friendly transportation that encourages the use of renewable energy. The problem of using electric bicycles began to emerge when there was a debate about the classification of electric bicycles as vehicles between several parties opposing the use of electric bicycles on the highway by several related parties. This study aims toknowing the legal regulations regarding the use of electric bicycles on sidewalks and legal certainty regarding the use of electric bicycles on sidewalks. This study uses a normative legal research methodology, namely an approach through the perspective of existing norms or in other words, a study in the form of an inventory of applicable laws. Legal regulations regarding the use of electric bicycles on sidewalks are specifically contradictory to Article 284 of Law Number 22 of 2009 concerning traffic and road transportation with Article 5 paragraph (4) of the Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 45 of 2020 concerning certain vehicles using electric drives where the use of sidewalks is generally regulated in Law Number 22 of 2009 concerning Traffic and Road Transportation. Legal certainty regardinguse of electric bicycles on the sidewalkis not yet providing legal certainty because it still raises speculation in its application, between the application based on the principle of lex specialist degorat legi or its application based on the principle of Lex Superior Derogat Legi Inferiori considering that the urgency of the impact of using electric bicycles on the sidewalk can harm one party, so this conflict of norms certainly hinders the purpose of forming a policy, one of which is legal certainty.